(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article analyzes the 1998 financial crisis in South Korea and the 2000s financial crises in Turkey from a historical and economic perspective, examining their recovery strategies through a comparative approach. The study evaluates the causes of the crises, the role of international financial institutions (IMF, World Bank), as well as the effectiveness of domestic policies and structural reforms. Drawing on practical experience and international literature, the article highlights the importance of post-crisis financial stability, institutional reforms, and economic diversification. The findings provide valuable insights for developing effective strategies to overcome modern economic crises for developing effective strategies to overcome contemporary economic crises.